The relationship of Dewey-type grade 1 malocclusion knowledge to the need for orthodontic treatment in children aged 9-12 years at SD Negeri Tamalanrea Makassar: Hubungan pengetahuan maloklusi kelas 1 tipe Dewey dengan kebutuhan perawatan ortodonti pada anak usia 9-12 tahun di SD Negeri Tamalanrea Makassar - Roynald Daniel Dendang; Muh. Harun Achmad (Makassar Dental Journal PDGI Makassar, 2024)
According to the 2018 Basic Health Research or Riskesdas, 57.6% of the Indonesian population admitted to having oral health problems. Patients with malocclusion in Indonesia are high despite the low demand for orthodontic treatment due to lack of knowledge about malocclusion. WHO defines malocclusion as an abnormality that can cause damage or interfere with occlusion function and may be an obstacle to the patient's physical and emotional health. This study aimed to determine the relationship between knowledge about malocclusion and the need for orthodontic treatment in children aged 9-12 years through quantitative research with descriptive observation method. The correlation coefficient value was obtained as 0.796. This shows that there is a very strong positive relationship between the level of knowledge of Tamalanrea State Elementary School students aged 9-12 years with malocclusion. In addition, a significance value of 0.002 (<0.01 or 0.05) was also obtained, which means that there is a significant relationship between knowledge and the incidence of malocclusion. It is concluded that there is a significant relationship between children and parents' knowledge and the incidence of malocclusion in children.